PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM JII PERIODE 2012-2021 - Hanifa Budiwati Utami (2022)
This study aims to examine the influence of financial performance on JII stock prices for the period 2012-2021. Financial performance is measured using the ratio of Return on assets (ROA), Return on Equity (ROE), earnings per Share (EPS), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR). Where ROA, ROE, EPS, DER, and DPR are independent variabels and stock price as a dependenn variabel. The population in this study is Sharia stocks listed on The Jakarta Islamic Index (JII) during the period 2012-2021 which amounted to 30 companies. The number of samples used in this study as many as 7 companies were selected using purposive sampling method. This study uses secondary data in the form of financial statements using Panel Data regression analysis techniques. The results showed that EPS variabels have a positive effect on stock prices and ROA, ROE, DER, and DPR variabels have no effect on stock prices. This research is expected to contribute to potential investors in determining investment options in Islamic stocks, as well as in developing the Islamic capital market industry in Indonesia. Keywords: Stock Price, JII, Financial Performance